Sumber Daya Manusia, Sistem Pengendalian Internal Pemerintah, Teknologi Informasi, dan Kualitas Laporan Keuangan - Minta, Jesicha Isadora Illiony; Juliarsa, Gede (E-Jurnal Akuntansi, 2023)
This research aims to determine the influence of the Quality of Human Resources, the Government's Internal Control System and the Use of Information Technology on the Quality of Regional Government Financial Reports. This research uses a quantitative-associative method which is located at the West Manggarai Regency Regional Work Unit. The sample used was purposive sampling and data collection was carried out by distributing questionnaires. The data analysis technique used in this research is multiple linear regression analysis with the help of the Statistical Package for Social Sciences program. The research results show that the quality of human resources, the government's internal control system and the use of information technology have a positive and significant effect on the quality of the West Manggarai Regency government's financial reports. Keywords: Human Resources; Internal Control System; Information Technology; Financial Reports